(untitled) (Journal Of Educational and Psychological Researches, 2016)
The goal of this research to identify the effect of the probing questions in the collection of material literature with students of the Kurdish language department, to achieve the aim of the research, the researcher has chosen a sample from the students of third stage of the Kurdish language Department, Faculty of Education / Ibn Rushd as a field for the application of experiment.The number of sample reached (71) students divided into two groups represented two divisions of the experimental groups under study to the style of questions sounding by (35) students, and represented the other division of the control group, which studied in the way normal and by (36) students, as rewarded researcher between the two groups Search in academic achievement for parents variable, and the variable intelligence, and the final grades in the subject of Kurdish literature for the second phase of the academic year 2013-2014, and took the probationary period of two months, the researcher developed a test component of (20) items to choose the type of multi-has been characterized by honesty and consistency mediated It was (0,78), and when analyzing the results statistically using samples t-test (T- Test) for two independent samples show that there are differences animate statistically significant in favor of the experimental group that studied the literature on substance according to the method of sounding questions on the control group which studied according to the usual way.